SISTEM DAN PROSEDUR PENJUALAN KREDIT SEPEDA MOTOR PADA PT.SMART MULTI FINANCE KECAMATAN MELAK KABUPATEN KUTAI BARAT - Imam Nazarudin Latif, Didik Setyadi H Eddy Soegiarto (EKONOMIA, 2016)
The objective is to determine whether the application of accounting system and procedures for credit sales at PT.Smart Multi finance in Melak are in accordance with the internal control system and procedures on credit sales in theory Mulyadi.Data were collected through a questionnaire to provide question to the responden regarding internal control for the implementation of system and procedures for creditÂ  sales in PT.Smart Multi Finance.The data obtained were analyzed using methods Champion is by counting the number of â€œyesâ€.The final score is used to conclude whether the systems and procedures are in accordance with the credit sales companyâ€™s internal control theory mulyadi.The result showed that credit sales accounting is appropriate according to the internal control system and procedures on credit sales (Score 86,67%).